Enhanced role of adenosine A2A receptors in the modulation of LTP in the rat hippocampus upon ageing - Costenla, Ana Rita (2022)
© 2011 The Authors. European Journal of Neuroscience © 2011 Federation of European Neuroscience Societies and Blackwell Publishing Ltd